PENDEKATAN ARSITEKTUR REGENERATIF TERHADAP RUANG KULINER DAN SENI DI JALAN SABANG JAKARTA PUSAT - Larissa, Tamara; Sutisna, Sutarki (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Jalan Sabang is a legendary area in Jakarta that has undergone various transformations since the colonial era. As part of the cultural corridor connecting Monas to Bundaran HI, this area plays an important role in the city's social and economic interactions. The emergence of the COVID-19 pandemic has caused a decline in activity, resulting in the fading of cultural identity and the weakening of the function of space as a place for community gatherings. The shift in focus on the area has caused the degradation of the area's character as a dynamic community space. The irregularity of spatial planning due to the large number of unorganized street vendors (PKL) has caused various problems, such as narrowing of roads, congestion, decreased visual quality of the area, and reduced comfort for pedestrians. The lack of space for cultural expression, minimal green space, and weak management of the area have also weakened the quality of life and overall attractiveness of the area. This research aims to design culinary facilities combined with street art through a regenerative and adaptive architectural approach. The aim is to revive Jalan Sabang's role as an inclusive, sustainable public space rooted in local identity. The design strategy includes the integration of community space, creative space, a comfortable pedestrian circulation system, and environmentally friendly elements to revive the socio-economic function of the area. The methods used include literature studies, field observations, user interviews, and site analysis. The results of the study show that regenerative architecture principles including the use of local communities, food waste processing, and adaptive design play a role in reviving the socio-economic power of the area, increasing pedestrian comfort, and creating public spaces that are relevant to today's needs. Keywords: adaptive; community; culture; regenerative; sabang Abstrak Jalan Sabang merupakan kawasan legendaris di Jakarta yang telah mengalami berbagai transformasi sejak era kolonial. Sebagai bagian dari koridor budaya yang menghubungkan Monas hingga Bundaran HI, kawasan ini memiliki peran penting dalam interaksi sosial dan ekonomi kota. Timbulnya pandemi COVID-19 menyebabkan penurunan aktivitas, dan mengakibatkan memudarnya identitas budaya dan melemahnya fungsi ruang sebagai tempat berkumpul komunitas. Pergeseran fokus pada kawasan menyebabkan degradasi karakter kawasan sebagai ruang komunitas yang dinamis. Ketidakteraturan tata ruang akibat banyaknya Pedagang Kaki Lima (PKL) yang tidak tertata menimbulkan berbagai masalah, seperti penyempitan jalan, kemacetan, penurunan kualitas visual kawasan, dan berkurangnya kenyamanan bagi pejalan kaki. Kurangnya ruang ekspresi budaya, minimnya ruang hijau, dan lemahnya pengelolaan kawasan turut memperlemah kualitas hidup dan daya tarik kawasan secara keseluruhan. Penelitian ini bertujuan merancang fasilitas kuliner yang dipadukan dengan seni jalanan melalui pendekatan arsitektur regeneratif dan adaptif. Tujuannya adalah untuk menghidupkan kembali peran Jalan Sabang sebagai ruang publik yang inklusif, berkelanjutan, dan berakar pada identitas lokal. Strategi perancangan mencakup integrasi ruang komunitas, ruang kreatif, sistem sirkulasi pedestrian yang nyaman, dan elemen ramah lingkungan untuk menghidupkan kembali fungsi sosial-ekonomi kawasan. Metode yang digunakan meliputi studi literatur, observasi lapangan, wawancara dengan pengguna, dan analisis tapak. Hasil dari studi menunjukkan prinsip arsitektur regeneratif meliputi pemanfaatan komunitas lokal, pengolahan limbah makanan, dan desain adaptif berperan dalam menghidupkan kembali daya sosial-ekonomi kawasan, meningkatkan kenyamanan pedestrian, serta menciptakan ruang publik yang relevan dengan kebutuhan masa kini.